Leadership and Patient Satisfaction in a Tertiary Health Care System (2015)
Patient satisfaction is one of the best indicators for measuring the success of the services being provided in a health facility. This study investigates the leadership factors that influenced patient satisfaction in the tertiary health care facility of the University of Benin Teaching Hospital, Benin City; Nigeria. This hospital based cross-sectional study was anchored on the social action theory, Talcott Parsons sick role model and concept of bureaucracy. Using a multi-stage sampling technique, 420 inpatients were randomly selected from five different units .(Medical, Surgical, Pediatrics, Obstetrics, and Gynecology and Emergency) of the hospital. Data was collected using semi-structured questionnaire and five in-depth interviews (IDls). Quantitative data were analyzed at univariate and bivariate levels, using descriptive statistics and Chi-square test while qualitative data were content analyzed. Findings revealed that there were good knowledge and level of awareness of the services available. Majority of the patients claimed that they were satisfied and rated the satisfaction experiences as moderate satisfaction with the health care services of the professional doctors and nurses in the hospital. Education (p<0.020) and income (p<0.032) were found to be significant socio-economic factors influencing patient's satisfaction. Answers doctors provided to patients' questions and prescribed drug administration by nurses to the in-patients were derivable from the leadership factors and thus influenced patient's satisfaction with the health care services. Results on answers doctors provided to patients' question (p<0.001) and prescribed drug administration by nurses to the in-patients (p<0.0073) were significant leadership factors. Similarly, from the qualitative data, doctor's communication and interaction greatly influenced patient's satisfaction with leadership ethos of health care providers. Management should organize stakeholder's forum comprising of doctors and nurses' leaders from among the health care providers and in-patients with common health conditions where subjective needs assessment of patients could be discussed within the hospital.